2022
DOI: 10.1002/path.5889
|View full text |Cite
|
Sign up to set email alerts
|

Cellular context determines DNA methylation profiles in SWI/SNF‐deficient cancers of the gynecologic tract

Abstract: SWI/SNF (SWItch/Sucrose Non-Fermentable) complex deficiency has been reported in a wide variety of cancers and is often associated with an undifferentiated phenotype. In the gynecologic tract SWI/SNF-deficient cancers are diagnostically challenging and little is known about their cellular origins. Here we show that undifferentiated endometrial carcinoma (UDEC), SMARCA4-deficient uterine sarcoma (SDUS), and ovarian small cell carcinoma, hypercalcemic type (SCCOHT) harbor distinct DNA methylation signatures desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
(26 reference statements)
2
8
0
Order By: Relevance
“…Our findings are consistent with prior DNA sequencing studies of SCCOHT which did not identify mutations or significant copy number variations in TP53 6–8 . Our results show that an abnormal p53 staining pattern renders a diagnosis of SCCOHT highly unlikely.…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are consistent with prior DNA sequencing studies of SCCOHT which did not identify mutations or significant copy number variations in TP53 6–8 . Our results show that an abnormal p53 staining pattern renders a diagnosis of SCCOHT highly unlikely.…”
Section: Figuresupporting
confidence: 91%
“…Our findings are consistent with prior DNA sequencing studies of SCCOHT which did not identify mutations or significant copy number variations in TP53. [6][7][8] Our results show that an abnormal p53 Correspondence 155 staining pattern renders a diagnosis of SCCOHT highly unlikely. Instead, immunohistochemical evidence of TP53 mutations would suggest other highgrade ovarian neoplasms, such as a high-grade serous carcinoma or even metastatic disease.…”
Section: Supporting Informationmentioning
confidence: 69%
“…Cancer cells harbour DNA methylation profiles that reflect both the cell of origin and somatically acquired DNA methylation changes 40 . We have previously shown that this technique allows the tracing of the distinct cellular origins of various cancers in the gynaecological tract 41–43 . In the current study, we show that teratoma‐associated ovarian WTs mostly share a DNA methylation cluster with mature cystic teratomas, which is distinct from primary renal WT (including three renal WT with DICER1 alterations).…”
Section: Discussionsupporting
confidence: 55%
“…40 We have previously shown that this technique allows the tracing of the distinct cellular origins of various cancers in the gynaecological tract. [41][42][43] In the current study, we show that teratoma-associated ovarian WTs mostly share a DNA methylation cluster with mature cystic teratomas, which is distinct from primary renal WT (including three renal WT with DICER1 alterations). Furthermore, the two so-called pure ovarian WTs clustered with the recently described DNA methylation cluster of SARC DICER1, which is distinct from both the clusters of primary renal WT and conventional DICER1-associated SLCT.…”
Section: Discussionmentioning
confidence: 49%
“…DNA methylation profiles of cancer cells reflect both somatically acquired DNA methylation changes and inherent features that reflect the cell of origin [15]. The latter enables, for example, the tracing of the distinct cellular origins in undifferentiated SWI/SNF (SWItch/Sucrose Non‐Fermentable)‐deficient cancers of the gynaecological tract [16]. Conversely, a significant overlap in the epigenome of tumours of various histological origins indicates a biological relatedness, as has recently been shown for DICER1‐associated neoplasms and for high‐grade endometrial stromal sarcomas with different types of genetic fusions [17,18].…”
Section: Introductionmentioning
confidence: 99%